2016
DOI: 10.1242/dev.130575
|View full text |Cite
|
Sign up to set email alerts
|

Wnt/β-catenin signaling enables developmental transitions during valvulogenesis

Abstract: Heart valve development proceeds through coordinated steps by which endocardial cushions (ECs) form thin, elongated and stratified valves. Wnt signaling and its canonical effector β-catenin are proposed to contribute to endocardial-to-mesenchymal transformation (EMT) through postnatal steps of valvulogenesis. However, genetic redundancy and lethality have made it challenging to define specific roles of the canonical Wnt pathway at different stages of valve formation. We developed a transgenic mouse system that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
34
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(44 citation statements)
references
References 89 publications
4
34
0
Order By: Relevance
“…While the effects of Wnt9b on sub-endocardial mesenchymal cell condensation are likely to be direct, we also observe changes in mesenchymal cell proliferation deep within the cushion mesenchyme following loss of endocardial Klf2 or Wnt9b that most likely reflect disruption of a still undefined chain of signals initiated by endocardial-mesenchymal cell WNT9B signaling. These studies confirm the proposed complexity of WNT signaling during valve development (Bosada et al, 2016; Gessert and Kuhl, 2010), and highlight the need to study this process in a highly specific spatio-temporal manner.…”
Section: Discussionsupporting
confidence: 76%
See 3 more Smart Citations
“…While the effects of Wnt9b on sub-endocardial mesenchymal cell condensation are likely to be direct, we also observe changes in mesenchymal cell proliferation deep within the cushion mesenchyme following loss of endocardial Klf2 or Wnt9b that most likely reflect disruption of a still undefined chain of signals initiated by endocardial-mesenchymal cell WNT9B signaling. These studies confirm the proposed complexity of WNT signaling during valve development (Bosada et al, 2016; Gessert and Kuhl, 2010), and highlight the need to study this process in a highly specific spatio-temporal manner.…”
Section: Discussionsupporting
confidence: 76%
“…Analysis of cushion gene expression revealed a nearly complete loss of Wnt9b and markedly reduced levels of the known canonical WNT target genes Axin2 and Lef1 , as well as the WNT inhibitory proteins Notum and Apcdd1 (Figure 5A-C and Figure S5). A complex and dynamic pattern of expression of WNT ligands has been reported in developing heart valves (Alfieri et al, 2010), and reporters have shown abundant canonical WNT activity in the remodeling cushion (Bosada et al, 2016; Gitler et al, 2003) as well as in abluminal cells adjacent to the endothelial cells lining the site of valve development in the zebrafish heart (Pestel et al, 2016), suggesting that WNT signaling may play an important role in this process. However, the precise role played by WNTs in the remodeling of cushions to mature valves and the mechanisms that regulate WNT expression in the remodeling cushion have not been defined.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In fact, it has been demonstrated that valvulogenesis continues after birth to adjust to the postnatal maturation of the heart. WNT/b-catenin signalling is active during heart valve development 6 and has been reported in human MVD. 2,7 There are 19 WNT family members which signal through the canonical (via b-catenin) pathway but can also signal through non-canonical pathways.…”
mentioning
confidence: 93%